Pengembangan Brosur sebagai Sumber Pengetahuan bagi Masyarakat tentang Jenis Tumbuhan Obat Tradisional - Yudi, Yudi (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2024)
Brochures are a medium for conveying information to the general public in written form. The main aim of this research is to develop a brochure to be used as a source of knowledge for the public about types of traditional medicinal plants. This type of research is development research. The development research in this research is making brochures for the community. The development model used is the 4D model developed by Thiagarajan et al. (1974) which consists of 4 stages, namely define, design, develop, and disseminate. However, in this research, the researcher modified it to 3D, namely define, design, and develop due to limited time and research level. The population for the development research was the entire community in Batu Bangka Village, Moyo Hilir District, Sumbawa Besar Regency. The sample for the development research was 15 people in Batu Bangka Village, Moyo Hilir District, Sumbawa Besar Regency. The data collection techniques used are validation, readability testing, and documentation. Based on the research that has been carried out, it was found that the validation results for content/material experts were 82% with very good qualifications, the validation results for language experts were 85% with good qualifications, and the validation results for display experts were 80% with good qualifications. Meanwhile, the highest public readability test results were 82% and the lowest public readability test results were 70%, so it can be said to be suitable for dissemination to the public.